2012
DOI: 10.1039/c2cc31887c
|View full text |Cite
|
Sign up to set email alerts
|

Residue choice defines efficiency and influence of bioorthogonal protein modification via genetically encoded strain promoted Click chemistry

Abstract: GFP and a FRET compatible dye were used to assess the influence of genetically encoded aryl azide positioning on Click chemistry-based protein conjugation. While modification efficiency of the sampled mutants using a strain promoted reaction varied by as much as ∼10 fold, there was no simple correlation with accessibility of the aryl azide on GFP's surface. One labeled GFP mutant (Gln204AzPhe) exhibited high efficiency FRET (∼90%) and an unprecedented pseudo-Stokes shift of 126 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 25 publications
(26 reference statements)
1
65
0
Order By: Relevance
“…It has been reported that higher solvent-accessibility of a NNAA generally ensures higher conjugation efficiency [6971]. However, it should be noted that NNAA substitution for an original amino acid with a fairly different structure and charge may undermine the accessibility-efficiency correlation [72]. Therefore, AzF incorporation sites, W160 and W174, were chosen out of amino acids bearing an aromatic ring, i.e., Phe, Trp, and Tyr, as well as high solvent accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that higher solvent-accessibility of a NNAA generally ensures higher conjugation efficiency [6971]. However, it should be noted that NNAA substitution for an original amino acid with a fairly different structure and charge may undermine the accessibility-efficiency correlation [72]. Therefore, AzF incorporation sites, W160 and W174, were chosen out of amino acids bearing an aromatic ring, i.e., Phe, Trp, and Tyr, as well as high solvent accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…The most highly reactive site ( k 2 = 17.8 M −1 s −1 ) had the least surface exposure of all tested sites and was in a non-charged but polar local environment with an adjacent aromatic phenylalanine residue. [22] …”
Section: Discussionmentioning
confidence: 99%
“…[39] Interestingly, DIBO appeared to have drastically reduced background labeling as compared with BCN and DIBAC. [39] Previous applications of SpAAC for site-specific protein labeling primarily involved highly expressing, soluble proteins such as GFP expressed in E. coli and purified by Ni-NTA affinity chromatography followed by one of two alternative schemes: i) incorporation of azF into the target protein and subsequent labeling with DBCO (a cyclooctyne closely related to DIBAC), [40] or ii) incorporation of BCN derivative of pyrrolysine followed by labeling with an azido-containing label. [41] …”
Section: Discussionmentioning
confidence: 99%
“…[16a, 31b] A similar effect has been observed for the modification of GFP using a similar cyclooctyne reagent. [40] A straightforward explanation would be that the lipophilic nature of DIBO, [31b] which enables the labeling reagent to partition into the dodecyl maltoside micelles, results in an increased local concentration at sites located in the hydrophobic region of rhodopsin.…”
Section: Discussionmentioning
confidence: 99%